No evidence for a single oscillator underlying discrete visual percepts. (28th June 2021) - Morrow, Audrey; Samaha, Jason
Abstract: Theories of perception based on discrete sampling posit that visual consciousness is reconstructed based on snapshot‐like perceptual moments, as opposed to being updated continuously. According to a model proposed by Schneider (2018), discrete sampling can explain both the flash–lag and the Fröhlich illusion, whereby a lag in the conscious updating of a moving stimulus alters its perceived spatial location in comparison to stationary stimulus. The alpha‐band frequency, which is associated with phasic modulation of stimulus detection and the temporal resolution of perception, has been proposed to reflect the duration of perceptual moments. The goal of this study was to determine whether a single oscillator (e.g., alpha) is underlying the duration of perceptual moments, which would predict that the point of subjective equality (PSE) in the flash–lag and Fröhlich illusions are positively correlated across individuals. Although our displays induced robust flash–lag and Fröhlich effects, virtually zero correlation was seen between the PSE in the two illusions, indicating that the illusion magnitudes are unrelated across observers. These findings suggest that, if discrete sampling theory is true, these illusory percepts either rely on different oscillatory frequencies or not on oscillations at all. Alternatively, discrete sampling may not be the mechanism underlying these two motion illusions or our methods were ill‐suited to test the theory. Abstract : ∎